THE ROLE OF ECONOMIC LITERACY IN HUMAN RESOURCE MANAGEMENT TOWARDS FINANCIAL INDEPENDENCE FOR MANAGEMENT STUDY PROGRAM STUDENTS AT SATYAGAMA UNIVERSITY - Dewi Sulistyani; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2024)
This study aims to analyze the role of economic literacy in human resource management towards financial independence for students in the Management Study Program at Satyagama University. The research method used a quantitative approach through the distribution of questionnaires to students as research respondents. The results show that students with a good level of economic literacy tend to be more able to manage their finances effectively, are disciplined in managing expenses, and have wiser financial behavior. Economic literacy also plays a crucial role in developing independent, productive human resources who are ready to face future economic challenges.